A Static and Snapthrough Analysis of an Innovative Bistable Composite Wing - Hijazi, Sara (2022)
A Master of Science thesis in Mechanical Engineering by Sara Hijazi entitled, “A Static and Snapthrough Analysis of an Innovative Bistable Composite Wing”, submitted in December 2022. Thesis advisor is Dr. Samir Emam. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).